Autonomization of Goals by Businesses on The Hotel Market: Selected Issues - Daniel SZOSTAK (Communications of International Proceedings, 2021)
The economic literature describes the “detachment” of an organization from its original purpose referring to it as the autonomization of goals. Once the process starts in a company, it involves the restructuring of the company’s strategy and building it anew. While autonomizing their goals, organizations may take different paths. The process can also be seen in businesses on the contemporary globalized hotel market. There are a number of companies whose operating modes have been transformed toward the autonomization of their goals, or the implementation of a different function instead of the original one.
Keywords: Autonomization Of Goals; Hotel Market; Survival and Development.